2014
DOI: 10.1002/pts.2085
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Prediction of the Lag Times of Hydrocarbons through a Polyethylene Terephthalate Film

Abstract: Polymeric materials can be used as functional barriers to prevent contamination of food from the environment or from other packaging components, e.g. mineral oil hydrocarbons from printing inks. Polyethylene terephthalate (PET) is such a promising barrier material. From permeation studies found in the scientific literature lag times, diffusion coefficients or permeation rates towards organic chemicals could not derived because of the slow diffusion process of the permeants in PET. Knowledge about lag times or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 18 publications
5
17
0
Order By: Relevance
“…The partition coefficient can be derived from the slope of the asymptote according to Equation 2. 13 The factor A within this equation is the area (typically expressed in cm 2 ) whereas I (in cm) is the thickness of the tested polyamide membrane. The upstream concentration of the permeant in the permeation cell is c gas phase ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The partition coefficient can be derived from the slope of the asymptote according to Equation 2. 13 The factor A within this equation is the area (typically expressed in cm 2 ) whereas I (in cm) is the thickness of the tested polyamide membrane. The upstream concentration of the permeant in the permeation cell is c gas phase ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore the barrier performance of various packaging films has been investigated recently. [11][12][13][14][15] Following these studies, polyamide-6 (PA6) as well as polyethylene terephthalate (PET) used as inner liners of cardboard containers showed very good barrier properties towards mineral oil contamination. For example, Fiselier and Grob 11 reported that 20 μm PA (cast) as well as 12 μm PET films show good barrier properties towards MOSH and MOAH.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The permeation curves were found to be very similar with results of Apostolopoulos and Winters, indicating that a high concentration gradient of organic vapours increased the rate of diffusion and had much shorter lag time, thereby allowing the system to reach equilibrium even faster. The method applied by Ewender and Welle was able to simulate the permeation rates by use of diffusion modelling, which determined the lag times for n‐alkanes through high‐barrier PET films. This study showed that the investigated PET film had good barrier properties toward organic contaminants.…”
Section: Introductionmentioning
confidence: 99%